Social-Skill Training to Improve Social-Skills of Student with Hearing Impairment - Ida Ayu Made Diah Naraswari; Kadek Suranata; Ni Ketut Suarni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study aims to describe the implementation of social skills training to improve social skills of students with hearing impairment. Subject in this study was a female student with hearing impairment who showed deficits in several aspects of social skills which caused her to experience difficulties in establishing social relationships. the intervention was carried out through the SST method which focused on developing three components of social skills, namely 1) creating positive interactions, (2) making friendship, and (3) recognizing one's emotions and ways to manage negative ones. 30 items of SSQ are used to measured social skills score before and after the intervention. Furthermore, observations were also used to described behavioral targets related to social skills that had been achieved through social skills training. The results of this study found that there was an increase in SSQ scores before and after the intervention was carried out, as well as changes in behavioral targets related to the aspects of social skills. The results of this study have implications for the implementation of guidance and counseling services in schools, especially in providing interventions for students with special needs.